Thermal and chemical stability of the β-W2N nitride phase. (August 2017) - Mateus, R.; Sequeira, M.C.; Porosnicu, C.; Lungu, C.P.; Hakola, A.; Alves, E.
Highlights: Pure Be, W and Be:W mixed coatings were deposited on silicon plates and implanted at room temperature with 30 keV N + ions with fluences up to 5e17 ions/cm 2 . Ion beam and X-ray diffraction analysis evidenced the formation of the α-Be3 N2 and β-W2 N nitrides. The identified tungsten nitride phase evolves from a BCC W lattice to a BCC W(N) solid solution after irradiating at a fluence of 1e17 N + /cm 2 and to the compact FCC β-W2 N structure at 5e17 N + /cm 2 . Thermal stability of β-W2 N was investigated by annealing the coatings for 1 h up to 1073 K. The results point to the release of non-bonded nitrogen solute in β-W2N over the annealing range and to the thermal stability of the nitride phase up to 1073 K. Abstract: Pure Be, W and Be:W mixed coatings with nominal compositions of (5:5) and (1:9) were deposited on silicon plates and implanted at room temperature with 30 keV N + ions with fluences up to 5e17 ions/cm 2 . Ion beam and X-ray diffraction analysis evidenced the formation of the α-Be3 N2 and β-W2 N nitrides. The identified tungsten nitride phase evolves from a BCC W lattice to a BCC W(N) solid solution after irradiating at a fluence of 1e17 N + /cm 2 and to the compact FCC β-W2 N structure at 5e17 N + /cm 2 . Thermal stability of β-W2 N was investigated by annealing the coatings for 1 h up to 1073 K. The results point to the release of non-bonded nitrogen solute in β-W2 N over the annealing range and to the thermal stability of the nitride phase up to 1073 K.